Current-induced spin-orbit effective field modulations in synthetic antiferromagnetic structures - Krishnia, Sachin (2021)
We demonstrate the modulation of spin-orbit torque (SOT) fields in synthetic antiferromagnetic (SAF) structures sandwiched between two heavy metals of opposite spin Hall angles. The SOTs fields that are measured by using harmonic Hall voltage technique, increase with net areal magnetization of the Pt/SAF/Ta structures. The result suggests an antiparallel orientation of the SOT fields in the two ferromagnetic layers. The antiparallel alignment of the SOT fields switches the magnetization of SAF structures with a current density as low as 2.3 × 1011 A/m2.